2018
DOI: 10.2478/rjim-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

How much bloating in the irritable bowel syndrome?

Abstract: The irritable bowel syndrome (IBS) is the most common chronic gastrointestinal disorder referred to gastroenterologists. One of the most common manifestations of IBS is bloating. Abdominal bloating is defined as subjective sensation of abdominal distension associated with girth increment. Therefore, it is described in the Rome IV criteria as bloating/abdominal distension. Bloating symptoms are reported by 10-30% of the general population and it was rated as the most bothersome symptom by 60% of IBS patients; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…1 Similar data has been reported from Romania. 13 These data suggested that besides recurrent abdominal pain, abdominal bloating should also be included in the IBS diagnostic criteria, while the pain component in IBS may be de-emphasized in Asia.…”
Section: Team 1: Symptoms and Epidemiologymentioning
confidence: 99%
“…1 Similar data has been reported from Romania. 13 These data suggested that besides recurrent abdominal pain, abdominal bloating should also be included in the IBS diagnostic criteria, while the pain component in IBS may be de-emphasized in Asia.…”
Section: Team 1: Symptoms and Epidemiologymentioning
confidence: 99%
“…Bloating in English is defined as the subjective sensation of an increase in abdominal girth, while abdominal distension is the visible or true increase in abdominal girth 1 . The first one is a symptom, while the second one is both a symptom and a clinical sign.…”
Section: Introductionmentioning
confidence: 99%
“…
Bloating in English is defined as the subjective sensation of an increase in abdominal girth, while abdominal distension is the visible or true increase in abdominal girth. 1 The first one is a symptom, while the second one is both a symptom and a clinical sign. In addition, bloating and distension can coexist and they are very commonly reported by patients and subjects in the general population.
…”
mentioning
confidence: 99%
“…Median percentage of days with bloating was lower in patients with IBS-C in the B. clausii group versus placebo. Bloating is common in IBS [ 46 ]. However, two RCTs showed that other probiotics did not impact the rate of bloating versus placebo (relative risk 0.32; 95% CI 0.04–2.56) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%